Comparative evaluation of clinical, hematological and systemic inflammatory markers in smokers and non-smokers with chronic periodontitis - Vinayak Kanakdande; Kaustubh P Patil; Abhishek Singh Nayyar (Wolters Kluwer Medknow Publications, 2015)
Context: Systemic conditions, especially chronic infections, have a direct impact on the general health and well-being of an individual. Similarly, the long-standing inflammatory changes seen during periodontitis have been associated with the altered diabetic control, preterm, low birth weight infants, and cardiovascular disease. Being a low-grade infection, the signs may not be as severe as seen in other systemic conditions, but they definitely cannot be ignored. Aims: The present study was designed to compare clinical, hematological, and systemic inflammatory markers in patients with chronic periodontitis. Subjects and Methods: A total of 90 chronic periodontitis patients were selected for the present study from the outpatient department of the Department of Periodontology, and the various clinical and hematological parameters were then assessed. Statistical Analysis Used: Z-test was used to compare the probing depth, clinical attachment loss, hematological parameter, and interleukin-6 values between Group A and Group B. Mann-Whitney U-test was used to compare gingival index, plaque index, and bleeding on probing between Group A and Group B. Results: The results of the study were based on the comparison of the clinical, hematological, and systemic inflammatory markers in smokers and nonsmokers with chronic periodontitis and came out to be statistically highly significant. Conclusions: With the resurgence of emphasis on significance of oral diseases related to systemic health, the medical professionals also need to familiarize themselves with the oral cavity and the oral-systemic inter-relationships to treat or reduce the morbidity of the underlying medical condition. Furthermore, the oral health care professionals must reach out to the medical community and the general public to improve patient care through education and communication about the oral health-systemic health link.